2016
DOI: 10.4103/1793-5482.145088
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioglioma of conus medullaris in a patient of neurofibromatosis type 1: A novel association?

Abstract: Ganglioglioma of the conus region is quite rare with only 12 reported cases. Ganglioglioma shares biologic features with neurofibromatosis leading to suggestions that the co-existence of the two diseases may be more than coincidental. We report a case of ganglioglioma of the conus medullaris in a patient of neurofibromatosis and explore the possible association of the two diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 12 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…[ 4 ] The most common location in the spinal cord is the cervical and the thoracic portions, covering 4–8 vertebral segments. [ 10 , 19 ] The mean lag time between onset of symptoms and confirming diagnosis of the tumor is 12 months. [ 10 , 19 ] There are no unique radiological features for gangliogliomas, however, MRI is very useful for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 4 ] The most common location in the spinal cord is the cervical and the thoracic portions, covering 4–8 vertebral segments. [ 10 , 19 ] The mean lag time between onset of symptoms and confirming diagnosis of the tumor is 12 months. [ 10 , 19 ] There are no unique radiological features for gangliogliomas, however, MRI is very useful for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Finally, in the fourth case, the authors described a ganglioglioma of the conus medullaris in a 16-year-old male (India, 2016). [ 19 ] The present report is the fifth documented case of the association of a spinal ganglioglioma in a patient with NF1 [ Table 1 ]. The aim of this paper is to add data to the literature regarding this rare association.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sunder et al reported a case of conus ganglioglioma who had associated neurofibromatosis type 1. 5 Sandeep et al could find 15 reported cases of ganglioglioma of the conus medullaris and added one of their own. 6 Usually the patients present with pain, paraparesis, gait ataxia, sensory disturbances, and bowel or bladder dysfunction.…”
Section: Discussionmentioning
confidence: 99%